MULTI-POTENTIALITY IN MICHAEL AVALLONE’S NOVEL KRAKATOA EAST OF JAVA - Alimsyah Alimsyah; Jumino Suhadi; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2017)
Abstract The research is about the protagonist’s multi-potentiality with three points of analysis: multi-potentiality in career, in self-discipline and making friend. Multi-potentiality exists when strong genetics and a desire to practice come together to create superior ability. Discipline means order or code of behaviour. Self-discipline refers to the ability to control one’s own feeling is very important. Self-Discipline leads to overcome one’s own weaknesses. Life without Self-discipline is no life. There are many valuable things in life, but friendship may be one of the most important. To live life without the experience of friendship is life without living. Human interaction is a necessity to survival, but developed friendships are essential to the successful well being of anyone. True friendship is a feeling of love, sharing and caring. The theory of multi-potentiality is proposed by Timoty (2008) stating that from knowledge and skills comes multi-potentiality, a set of personal characteristics that enhance one’s ability to achieve expertise in an accelerated manner. These traits allow one to improve at quicker rates than others in their field that are at the same level of expertise. Descriptive qualitative method by Bickman (2010) is applied to analyze all the data concerning multi-potentiality and conducted to demonstrate association or relationships between things in the world around us in this matter, significant events in the novel and how all the events are molded into a story. The result shows that the protagonist has multi-potentiality in the forms of ability in career, self-discipline and making friends. Keywords: self-discipline, potentiality, career